(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1856)
A medieval coining iron was exhibited alongside a coin from the die itself. The author argues that these objects are from the reign of Alexander III. He goes on to discuss the manufacture of coinage, concluding that we do not have sufficient evidence to determine that this die was from an official royal mint and suggested that it may have been a forger’s tool.